Risiken und Gefahren von Marktmacht in digitalen Märkten - eine wettbewerbspolitische Analyse - Milczarek, André

Tax Avoidance - Are Banks Any Different? - Müller, Jens; Gawehn, Vanessa

Fabrication of Lyotropic Alignment Layers for Thermotropic Liquid Crystals Facilitated by a Polymer Template - Zhang, Bingru; Schmidtke, Jürgen; Kitzerow, Heinz-Siegfried (Advanced Optical Materials)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Improved organic thin-film transistor performance by dielectric layer patterning - Temme, Julian; Meyers, Thorsten; Reker, Julia; Vidor, Fábio F.; Vollbrecht, Joachim; Kitzerow, Heinz-Siegfried; Paradies, Jan; Hilleringmann, Ulrich (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Method for Analysing Requirement Change Propagation based on a Modified Pagerank Algorithm - Gräßler, Iris; Thiele, Henrik; Oleff, Christian; Scholle, Philipp; Schulze, Veronika (Proceedings of the Design Society: International Conference on Engineering Design)
Complexity of products and systems is increasing through digitalization, interdisciplinarity as well as high technology maturity and new business models. In consequence, new product development (NPD) projects need to manage and satisfy a large number of requirements from a broad range of stakeholders. Yet, NPD projects are often delayed due to requirement changes. In this paper, a new method for analyzing requirement change propagation is presented. The method is based on the assessment of requirement interrelations structured in a requirements structure matrix by a modified page-rank algorithm. By the method, a high number of strongly interrelated requirements can be analyzed in an efficient manner. Additionally, higher-level interrelations as well as the relative weights of requirements are also incorporated in the analysis. Hereby, an efficient holistic approach towards the analysis of requirement change propagation is proposed.

Role Model for Systems Engineering Application - Gräßler, Iris; Oleff, Christian; Hentze, Julian (Proceedings of the Design Society: International Conference on Engineering Design)

Peters, Robert (2017). Atlas spätmittelalterlicher Schreibsprachen des niederdeutschen Altlandes und angrenzender Gebiete (ASnA). - Wallmeier, Nadine (Zeitschrift für Rezensionen zur germanistischen Sprachwissenschaft)

Pawel Pieranski – crystallographer of liquids and Alfred-Saupe-prize laureate 2019 - Kitzerow, Heinz-Siegfried (Liquid Crystals Today)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Mit Droste im Glashaus - 21 Künstlerinnen und Künstler werfen Blicke - Morrien, Rita (Mit Droste im Glashaus. Scherbensammlung)

Luxuskörper – Die Diva und das Geld - Grotjahn, Rebecca (Journal Netzwerk Frauen- und Geschlechterforschung NRW)